RESET-REliability and Safety Engineering and Technology for large maritime engineering systems - (:unkn) unknown (My University, 2026)
August 2016-present: Participation in the H2020-MSCA-RISE-2016 program: ‘RESET-REliability and Safety Engineering and Technology for large maritime engineering systems’. Extended participation in the preparation phase of the proposal; participation in all WPs; leader in WP4.